Studies in Experimental Animals on Disseminated Intravascular Coagulation (DIC) - Markwardt, F; Nowak, G; Meerbach, W; Rüdiger, K.-D (Thrombosis and Haemostasis, 1975)
Changes in the clotting system, as well as morphological and functional alterations corresponding to that of the pathologic phenomenon of disseminated intravascular coagulation (DIC) or consumption coagulopathy, were produced by thrombin infusion (550 NIH U × kg−1 × h−1) in rats and simultaneous inhibition of fibrinolysis by PAMBA (100 mg/kg).Changes in the fibrinogen level and platelet count as well as the appearance of fibrin monomers and the formation of microthrombi in several organs were evaluated. Simultaneously, the function of the respiratory system was investigated by continuous measurement of oxygen consumption as well as elasticity and water content of the lung. From the time course of the alterations in the several parameters, conclusions can be drawn for the pathogenesis and the possible therapeutic influence on DIC.